Unity and National Development in Nigeria: A Paradox - Ephraim Ahamefula Ahamefula Ikegbu; Maduka Enyimba; Grace Ogelenya (Universitas Negeri Makassar, 2018)
Nigeria with well over 350 ethnic nationalities is constitutionally a secular state. The secularity of Nigeria implies that within the framework of the law, people are to undergo their businesses without being restricted to a particular parochial or primordial arrangement. But in spite of this position, monumental frictions which have impaired developmental pedestal of Nigerian state are on high scale. Philosophy has identified unity as the major springboard to navigate development both at the individual and the state level. Apart from philosophy identifying unity as a tool for peace and progress, the Nigerian state underscores the values of unity that it reflects it in the Nigeria’s coat of arms. The need for unity also has expression in the national anthem and the pledge which is sworn to by every citizen at any given time the need arises. Inspite of these concerted efforts at ensuring unity, Nigerian state is still found in the deep sea of disunity. This ugly phenomenon has adversely affected development in the country. No tremendous progress is likely to be recorded by any nation state faced with the problem of disunity. This paper is of the view that ethnicity, tribalism, corruption, electoral fraud, bad leadership, immorality, contract inflation, “sit tight” government and others are very many issues that promote disunity in the Nigerian state, and these ugly phenomena do not allow the nation state to advance pragmatically in all the spheres of existence. This paper submits that national re-orientation, enlightenment campaign and spiritual and/or moral rebirth are not only therapeutic but a condition-sine-qua- non for national integration.